E-gov na amazônia: a busca por um governo mais transparente e democrático - ASSIS, Gustavo Bento de (Universidade Federal do Pará, 2017)
This study investigates the portals of state governments in the Amazon , sando saw the realization of e-government movements who want to deepen democracy through digital processes. The investigation was conducted in six states portals Amazon. The analysis model encompasses, on the one hand, the most technology and how these portals are providing information to citizens aspects in order to create facilities and opportunities for their lives. And secondly - and this is the most important aspect - those relating to accountability and popular participation. All this has the sense to see how the portals have been constituted as an instrument to deepen democracy in the Amazon states and realization of a new type of society: the digital. The theoretical model undertakes categories of e-government, accountability and popular participation. The results are not encouraging, also converging with international experience. What is observed is that the portals, in general, have adequate technological resources, there are conditions of good navigation, information search. Thus, the technology does not seem to be a problem. What portals resent really is greater interactivity, it can be inferred that the relations established are fundamentally the government-to-citizen type, with the government issuing and society, it seems, the receiver liabilities, while away the inversion of this relationship for citizen-to-government.